Readmissions for Morbidities among Women within the Puerperium - Raut, Bhaktabatsal (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: There are varieties of morbidities which occurs during the postpartum period. The type and severities of such morbidities will determine the need for hospital readmission and appropriate treatment. To analyze the maternal morbidities among postpartum women who have been readmitted following discharge from the hospital after delivery. MATERIAL AND METHODS: This was a hospital based descriptive study which was conducted including all women readmitted for postpartum complications within the puerperium after having been delivered at Paropakar Maternity and Women's Hospital, Thapathali, Kathmandu. The variables considered for study were pattern of postpartum morbidities, age and parity of women, mode of delivery and average duration of hospital stay. RESULTS: The incidence of maternal postpartum readmission after having been delivered in study hospital was 1.25% (n= 80), out of which puerperal sepsis was the most frequent diagnosis comprising 37.5% (n=30), followed by secondary PPH 30% (n=24), urinary tract infections and hypertensive disorders of pregnancy. Seventy percentage of women were within the age group of 20-29 yrs and 56.3% were primipara. When proportion of morbidities were analyzed among age groups of ≤19yrs and ≥ 20 yrs, and primiparity and multiparity, showed statistically insignificant difference. Sixty-six (82.5%) women had vaginal delivery and 14 (17.5%) had caesarean section. The percentage of readmission for postpartum morbidity among caesarean delivery was 1.43%, and in vaginal delivery, it was 1.22% . But this difference was statistically not significant (p value = 0.59).The average duration of hospital stay for postpartum morbidities was 4.53 days. CONCLUSION: The incidence of maternal readmission for postpartum morbidities after having been delivered in the study hospital was 1.25%, of which infectious morbidity was the commonest one. There is no statistically significant difference among morbidities between different age and parity groups. Women who had caesarean delivery were more likely to have postpartum morbidity requiring hospital readmission than women who had vaginal delivery but this difference was statistically not significant. Prevention and adequate treatment of infections in pregnancy, labor, delivery and postnatal period, and more stringent management of hypertensive disorders of pregnancy are mandatory to reduce the incidence of postpartum morbidity.